2021
DOI: 10.3390/polym13162719
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Abaca–Glass Fiber Composites Fabricated by Vacuum-Assisted Resin Transfer Method

Abstract: The application of natural fiber-reinforced composites is gaining interest in the automotive, aerospace, construction, and marine fields due to its advantages of being environmentally friendly and lightweight, having a low cost, and having a lower energy consumption during production. The incorporation of natural fibers with glass fiber hybrid composites may lead to some engineering and industrial applications. In this study, abaca/glass fiber composites were prepared using the vacuum-assisted resin transfer m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Further studies by Nallusamy and Majumdar [38] reported 53.8 and 39.0% increase in tensile and impact strengths, respectively, for jute/glass fibre hybrid composites compared with pure jute fibre reinforced epoxy counterparts. Reinforcing 50% date palm fibres in epoxy matrix increased the flexural strength and modulus of the resultant composite to 32.6 MPa and 3.3 GPa compared to 26.2 MPa and 2.3 GPa, respectively, for unreinforced epoxy composites [39]. Research has shown that the volume fraction of abaca and glass fibres and stacking sequence determine the mechanical properties of abaca/glass fibre hybrid reinforced composites [40].…”
Section: Commonly Used Natural Plant Fibres Inmentioning
confidence: 99%
“…Further studies by Nallusamy and Majumdar [38] reported 53.8 and 39.0% increase in tensile and impact strengths, respectively, for jute/glass fibre hybrid composites compared with pure jute fibre reinforced epoxy counterparts. Reinforcing 50% date palm fibres in epoxy matrix increased the flexural strength and modulus of the resultant composite to 32.6 MPa and 3.3 GPa compared to 26.2 MPa and 2.3 GPa, respectively, for unreinforced epoxy composites [39]. Research has shown that the volume fraction of abaca and glass fibres and stacking sequence determine the mechanical properties of abaca/glass fibre hybrid reinforced composites [40].…”
Section: Commonly Used Natural Plant Fibres Inmentioning
confidence: 99%
“…Taking GFRP as an example, the polymer matrix/glass fiber combination (a fiber volume fraction of 55–60 vol % is considered to be standard [6]) leads to versatile properties, such as chemical resistance, electrical insulation, high stiffness, high strength‐to‐weight ratio, long durability, and low weight, and is more cost‐effective to produce compared to CFRP [7, 8]. Accordingly, GFRP are used in numerous applications such as construction, automotive, aerospace, and wind turbine blade manufacturing [9–12]. On the other hand, their recycling poses technical and economic challenges, and therefore they have been landfilled and incinerated for decades [13].…”
Section: Introductionmentioning
confidence: 99%
“…Aside from abaca fiber, the next abundant natural fiber found in the Philippines is Pineapple leaf fiber (PLF) [10]. The Philippines ranks 3 in the world producer of pineapple [11].…”
Section: Introductionmentioning
confidence: 99%